2017
DOI: 10.1002/rcm.7920
|View full text |Cite
|
Sign up to set email alerts
|

Ozone‐induced dissociation on a traveling wave high‐resolution mass spectrometer for determination of double‐bond position in lipids

Abstract: Rationale The position of C=C within fatty acyl chains affects the biological function of lipids. Ozone induced dissociation-mass spectrometry (OzID-MS) has great potential in determination of lipid double bond position, but has generally been implemented on low resolution ion trap mass spectrometers. In addition, most of the OzID-MS experiments carried out so far were focused on the sodiated adducts of lipids, fragmentation of the most commonly observed protonated ions generated in LC-MS based lipidomics work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 42 publications
(56 reference statements)
4
46
1
Order By: Relevance
“…The OzID-MS experiments were performed on a modified Synapt™ G2 HDMS instrument (Waters, Manchester, UK) as reported previously [52]. Briefly, O 3 MEGA integrated ozone delivery system (MKS Inc., Andover, MA) was connected to the trap and transfer regions of the instrument through a three-way valve.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The OzID-MS experiments were performed on a modified Synapt™ G2 HDMS instrument (Waters, Manchester, UK) as reported previously [52]. Briefly, O 3 MEGA integrated ozone delivery system (MKS Inc., Andover, MA) was connected to the trap and transfer regions of the instrument through a three-way valve.…”
Section: Methodsmentioning
confidence: 99%
“…Traveling wave in the trap and transfer regions were operated at the following settings as optimized previously [52]: Entrance, 5.0 V; Bias, 2.0; Trap DC, 0.2; Exit, 0; trap wave velocity, 8 m/s; wave height, 0.2 V; transfer wave velocity, 247 m/s; wave height, 0.4 V. Default instrument settings for all the remaining parameters were applied. Under these settings, the reaction time between ozone and ions is estimated to be ~16.65 ms [52]. Instrument was calibrated daily in Resolution mode using sodium formate following manufacturer’s instructions obtaining less than 0.6 ppm (0.5 mDa) RMS residual mass.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that OzID is functional on chromatographic timescales, which is of importance for the separation of structural isomers by liquid chromatography (LC) and quantitative lipidomics [20,21]. Ozone was introduced to a high-pressure region of the mass spectrometer in order to perform online ozonolysis at the fatty acid double bonds [22,23]. Characteristic product ions, including radical cations, were produced from rapidly formed reaction products.…”
Section: +mentioning
confidence: 99%